Motor Control and Learning in Childhood and Adolescence Interactions with Sports and Exercise - Clemente, Filipe Manuel; Silva, Ana Filipa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book represents the articles published in the Special Issue "Motor Control and Learning in Childhood and Adolescence: Interactions with Sports and Exercise". Among the included articles, two main topics of research can be observed: those focusing on sports training and those focusing on exercise and physical activity for health. Interestingly, different study designs and methodologies were conducted, thus we believe that this book provides interesting reading for those who want to have a quick overview of the current research in motor control and learning.